2010
DOI: 10.1177/0092055x10378827
|View full text |Cite
|
Sign up to set email alerts
|

ASA’s Bachelor’s and Beyond Survey

Abstract: With the support of the National Science Foundation, the American Sociological Association conducted a longitudinal survey of sociology majors from the class of 2005, following them from senior year into careers or graduate school. The first part of this article provides a context for the results from the What Can I Do with a Bachelor's Degree in Sociology? study and a summary of its key findings. Wave I data demonstrate strong student interest in sociological concepts, perceived mastery of some research skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 12 publications
2
29
1
Order By: Relevance
“…Unless their training institutions or programs offer opportunities for practicing applied aspects of sociology, the majority of sociology students will experience applied aspects of sociology firsthand only after graduation. This chapter concurs with the view espoused by Spalter-Roth et al (2010) that the majority of students who undertake sociology majors at university do so because they want to understand the nature of society, the issues that plague it, and how these can be addressed. The fulfilment of this aspiration, particularly for students who prioritize the values of equality and nondiscrimination, can be best attained in the context of working with communities and groups, which, according to Finkelstein (2010, 100), constitute "the laboratory in sociology."…”
Section: Supporting the Case For Applied Sociologysupporting
confidence: 76%
See 1 more Smart Citation
“…Unless their training institutions or programs offer opportunities for practicing applied aspects of sociology, the majority of sociology students will experience applied aspects of sociology firsthand only after graduation. This chapter concurs with the view espoused by Spalter-Roth et al (2010) that the majority of students who undertake sociology majors at university do so because they want to understand the nature of society, the issues that plague it, and how these can be addressed. The fulfilment of this aspiration, particularly for students who prioritize the values of equality and nondiscrimination, can be best attained in the context of working with communities and groups, which, according to Finkelstein (2010, 100), constitute "the laboratory in sociology."…”
Section: Supporting the Case For Applied Sociologysupporting
confidence: 76%
“…Student pathways into group work and community action that are currently left unspoken would require clearer articulation and acceptance. Universities that currently offer students an applied sociology pathway see the merits of expanding into these social justice and community practice oriented domains (Finkelstein 2010;Spalter-Roth et al 2010). In a financially constrained environment where the survival of sociology as a discipline cannot be taken for granted, reaching out to related disciplines, especially social work and community work, may in the long term guarantee sociology's sustainability as a discipline.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the discipline of psychology, there is little known about the core admission requirements or their relative importance for those pursing graduate degrees in sociology. A review of the literature revealed mainly peer-reviewed studies on career trajectories after obtaining an undergraduate degree (e.g., see Guppy, Greer, Malette, & Frank, 2017;Spalter-Roth, Senter, Stone, & Wood, 2010;Vaughan, 1979). For example, Guppy, Greer, Malette, and Frank (2017) found that female graduates tend to hold positions in the community service, social work, teaching, and administration professions while males are more apt to be employed in the criminal justice system and the private sector.…”
Section: Sociology Graduate School Requirementsmentioning
confidence: 99%
“…They are not. In fact, racial minorities are underrepresented in the sociology major relative to presence in other undergraduate majors ( Chronicle of Higher Education 2014; Spalter-Roth et al 1996). The American Sociological Association documented that, following the onset of the Great Recession, fewer students who majored in sociology did so with beliefs that it was preparing them for future careers (Spalter-Roth et al 2012).…”
Section: The Impact Of Student Demographics and Student Interestsmentioning
confidence: 99%